HUBUNGAN HIGIENE SANITASI DENGAN KUALITAS MIKROBIOLOGIS PADA MAKANAN GADO-GADO DI KECAMATAN TEMBALANG KOTA SEMARANG - Yuniatun, Tuti; Martini, Martini; Purwantisari, Susiana; Yuliawati, Sri (Jurnal Kesehatan Masyarakat (Undip), 2017)
Gado-gado is one of traditional foods from Indonesia which sold in Tembalang District. Gado-gado is made from various vegetables mixed with peanut sauce, served at temperature 5-60oC which is the "temperature danger zone" for any food. This situation makes gado-gado such a watery yet not-so-hot food when its served, so has a potency to be contaminated by microbes and fungis. The purpose of this research is to understand correlation between hygiene sanitation and microbiological quality of gado-gado in Tembalang District, Semarang City. This research is observational research using cross sectional design and consists of three variables, namely sellers health condition, sellers hygienic practice, and places sanitation. The samples of this research are 36 gado-gado and respondents of this research are 36 gado-gado sellers which is observed their hygienic sanitation while processing gado-gado. Data were analyzed by frequency distribution and bivariate analysis using chi square. The results showed that sellers health condition categorized as good condition (88,9%); sellers hygienic practice categorized as good condition (33,3%); and places sanitation categorized as good condition (22,2%). There was statistically significant correlation between sellers hygienic practice (p=0,008) and places sanitation (p=0,028) with gado-gado microbiological quality. While there is no corrrelation between sellers health condition (p>0,999) with gado-gado microbiological quality.Gado-gado sellers should pay attention to their personal hygiene and the places sanitation when processing gado-gado, to improve gado-gado microbiological quality.